THE RUSSIAN FACTOR IN CENTRAL ASIAN GEOPOLITICS IN THE CONTEXT OF IRANIAN-AMERICAN CONTRADICTIONS - YULDASHEVA, Guli (CENTRAL ASIA AND THE CAUCASUS, 2007)
Russia’s Central Asian policy is one of the most debatable and pertinent issues that have been in the center of attention for some time now. In fact, it has acquired additional overtones in the context of the continued Iranian American confrontation, which affects Central Asian geopolitics and the Eurasian approach dominating Russia’s foreign policy (which presupposes Russia-IRI partnership in Central Asia). It is absolutely clear that the nature, content, and pace of Russia’s involvement in the region, as well as co-operation between the two countries, directly de-pend on the state and level of Iranian American relations. Russia’s devotion to the idea of multi-polar approaches to international relations is well known.1 In this context, its access to Central Asia’s energy resources and control over the transportation and communication corridors make it one of the leading centers of power of Eurasia. Its Central Asian geostrategy presupposes:— maintaining stability in all spheres—political, military, economic, humanitarian, and le- gal;— reintegrating the region on the basis of a new system of energy transportation and water com- munication across the Eurasian expanse;— developing a single economic zone, of which Central Asia will be a part; moving Russian companies to key positions in the Caspian;— strengthening its leadership in the emerging system of interstate political and economic rela- tions in Central Asia, etc. E. Kozhokin, Director of the Russian Institute of Strategic Research, has written in this connec-tion: “Russia needs political, economic, and social stability in the Central Asian region” and pointed out that Central Asia has an important role to play in Russia’s economy.2 Russia treats opposition to the radical extremism that threatens its stability, southern borders, and territorial integrity as a prior-ity. For this reason, and to ensure its geopolitical interests, Moscow is striving to play an important role in Afghanistan’s post-conflict stabilization.